ORAL MANIFESTATIONS IN PRIMARY PEDIATRIC VASCULITIS - Iuliana Magdalena Starcea; Ileana Katerina Ioniuc; Alice Nicoleta Azoicai; Roxana Alexandra Bogos; Tudor Ilie Lazaruc; Madalina Andreea Beldie; Ana-Maria Daniela Nistor; Diana Maria Cira; Anca Ivanov; Mirabela Alecsa; Tatiana Chisnoiu; Ionela Daniela Morariu; et al. (Romanian Society of Oral Rehabilitation, 2023)
Vasculitis are disorders characterized by the presence of an inflammatory process in the blood vessel wall, resulting in damage or necroses of certain tissues or organs. Numerous clinical symptoms, ranging from acute localized hypersensitivity reactions to severe auto-immune systemic disorders that are incurable and life-threatening, can be attributed to the types and locations of affected arteries as well as the level of inflammation. Typical oral or facial symptoms of several forms of vasculitis can help in an early diagnosis of vasculitis. IgA vasculitis and Kawasaki disease (KD) are the two predominant types of pediatric vasculitis that involve the mouth, followed by ANCA vasculitis. Furthermore, SLE, a connective tissue disease, is one of the most prevalent autoimmune illnesses in children and can proceed rapidly across multiple organs or start mildly and gradually. Numerous more systemic conditions, such as infection, autoinflammatory disorders and neoplasia, can also primary or secondary localize in the oral cavity, infections being more frequent. Many various professionals, including dentists, family physicians, pediatricians, rheumatologists, hematologists, gastroenterologists, and otorhinolaryngologists, examine and treat children with oral symptoms. In 87.7% of patients overall and over 90% of patients with KD and IgA vasculitis (formerly known as Henoch-Schönlein purpura), cutaneous involvement was observed. Recurrent oral aphthous ulcers were present in all Behçet syndrome patients (1).